Penyuluhan Pola Asuh Orang Tua Balita Dengan Masalah Gizi Di Desa Sampoang Tahun 2023 - Musdalifah Musdalifah (Jurnal Informasi Pengabdian Masyarakat, 2023)
Adequacy of nutrition and food is one indicator of the success of a nation's development. The nutritional status of children under five is one of the indicators used to measure the nutritional status of the community. Toddlers and infants are one of the age groups that are vulnerable to malnutrition. Nutrition is very influential on intelligence and work productivity. Malnutrition in toddlers can cause growth disorders and physical development and intelligence. The purpose of this activity is to increase knowledge about the parenting style of parents of toddlers with nutritional problems in Sampoang Village. This service activity is carried out in 3 stages, namely the preparation stage, the counseling stage and the closing stage by preparing a community service report. This activity was attended by 37 participants, during the implementation of the counseling, the presenters also conducted an evaluation by conducting a question and answer session with the counseling participants. This counseling gave significant results where there was an increase in knowledge of parents of toddlers by looking at the results of the evaluation given by conducting a question and answer session with counseling participants.